2014
DOI: 10.1117/12.2075442
|View full text |Cite
|
Sign up to set email alerts
|

Long-term trends of the critical frequency of the F2-layer of the ionosphere

Abstract: In the study the critical frequency of the F2-layer of the ionosphere data obtained at Ionospheric Observatory of Tomsk State University are analyzed. The analysis focuses on the study of the spectral composition and determining the longterm trends values of foF2. For the spectral estimation the anharmonic decomposition method is used. The result of research is establishing the dependence of a long-period trends character, periods values and the amplitudes of variations of foF2 values caused by the eleven-year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…Rishbeth & Mendillo (2001) found that the solar ionizing radiation, the solar wind/geomagnetic activity, and the meteorological effects are the likely causes of F2-layer variability. Spectral analyses of the long-term changes in the critical frequencies of F2 layers (foF2) and total electron content (TEC) confirm a dominant 11 yr solar cycle variation (Khaitov et al 2014;Tang et al 2014).…”
Section: Introductionmentioning
confidence: 93%
“…Rishbeth & Mendillo (2001) found that the solar ionizing radiation, the solar wind/geomagnetic activity, and the meteorological effects are the likely causes of F2-layer variability. Spectral analyses of the long-term changes in the critical frequencies of F2 layers (foF2) and total electron content (TEC) confirm a dominant 11 yr solar cycle variation (Khaitov et al 2014;Tang et al 2014).…”
Section: Introductionmentioning
confidence: 93%